Analysis of factors affecting intercultural communication awareness in generation Z - Wahdania; Ramadhan, Muh. Fauzi; Novia, Lely (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2026)
Intercultural communication awareness is a crucial competence for Generation Z in navigating an increasingly complex global environment. This study aims to analyze the factors affecting intercultural communication awareness among Generation Z, focusing on the intensity of cross-cultural interactions, communication comfort, cultural literacy, and the use of social media. A quantitative approach was used, employing a survey method involving over 100 university students from various institutions in Makassar. Data were collected through an online questionnaire covering ten key indicators. The findings reveal that most respondents frequently interact with individuals from different cultures and actively use social media to explore foreign cultures. Furthermore, they display a positive attitude in adapting their communication style and showing respect for cultural differences. However, challenges remain in avoiding cultural stereotypes and actively engaging in discussions about intercultural issues. The study concludes that exposure to different cultures through digital media and social interaction significantly enhances intercultural communication awareness. Multicultural education is needed to strengthen cross-cultural understanding and tolerance among Generation Z.